Editorial. Issue 1 (1st July 2021) - McCarthy, Conal
Abstract : After a tumultuous year around the globe in the wake of COVID 19, the cultural sector, including museums, galleries, and other institutions, as well as universities, have emerged in 2021 scathed but still functioning. As an academic journal engaged with professional museum practice, it is to be expected that Museum Worlds 9 will reflect the unprecedented impact of the pandemic. If the 2020 issue was difficult to collate and produce, this year's issue was doubly so: academics and students are busy, stressed, and preoccupied with teaching online, while museum professionals are overworked, or out of work, or at home with their museums closed, and there are few exhibitions and public programs. Even the publishing industry seems to have been severely affected: new titles have been delayed, it is tricky to get books sent to readers due to holdups with freight, and writers, reviewers, and editors are busy, busy, busy.